2020
DOI: 10.33824/pjpr.2019.34.4.43
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Modes, Strategies, and Psychosocial Consequences of Cyberbullying Perpetration and Victimization Among University Students

Abstract: The purpose of the study was to explore modes, strategies, and consequences of cyberbullying perpetration and victimization among university students. In-depth interviews of 14 volunteer university students (8 male and 6 female) were conducted who volunteered to participate in the study in which 10 participants were “cybervictims” whereas 4 were “cyberbully-victim”. Interview guide was used for conducting unstructured interviews. Thematic analysis of the interviews revealed different experiences in cyberspace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…The intense effects ranged from affecting mental health, difficulty in concentrating in the study, long absence in school to lowering of self-esteem, blaming oneself, isolating himself from the society. It also included extreme impacts like that of harming others, self-harm, and even committing suicide (Kanwal & Jami, 2019). The experience of cyberbullying is quite strenuous for the victims, and the intensity of the effects varies from person to person.…”
Section: Section IImentioning
confidence: 99%
“…The intense effects ranged from affecting mental health, difficulty in concentrating in the study, long absence in school to lowering of self-esteem, blaming oneself, isolating himself from the society. It also included extreme impacts like that of harming others, self-harm, and even committing suicide (Kanwal & Jami, 2019). The experience of cyberbullying is quite strenuous for the victims, and the intensity of the effects varies from person to person.…”
Section: Section IImentioning
confidence: 99%
“…Moreover, interaction with such an event that is perceived as trauma by an individual can alter his capability to arrange educational tasks priority-wise and practically attempt such educational tasks in the long term after the trauma experience (Bohannon et al, 2019). A significant amount of literature was available in Pakistani culture focusing on different traumatic events separately (Malik et al, 2018;Bibi et al, 2019;Kanwal & Jami, 2019;Ahmed et al, 2020). But no previous studies focused on the overall impact of traumatic events on social behavior.…”
Section: Social Behaviormentioning
confidence: 99%
“…It has also been observed that numerous victims, while they are suffering bullying, present low academic performance, difficulty concentrating and truancy. In the future they will be more vulnerable to stress, negative emotions such as fear and having suicidal thoughts [55,56].…”
Section: Frameworkmentioning
confidence: 99%